UPAYA MENINGKATKAN KEMAMPUAN MENULIS LAPORAN KARYA WISATA DENGAN MENERAPKAN METODE TUGAS INDIVIDUAL SISWA KELAS VIIIF SEKOLAH MENENGAH PERTAMA NEGERI 3 TABANAN TAHUN PELAJARAN 2012/2013 - Sueni, Ni Made; Wahyuni, Ni Wayan Sri Eka (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2014)
Teaching Indonesian should comprise a set of skills. One of the skills is a report writing skill through direct observation in the classroom. It can be seen, from the preliminary observation, that the students have difficulty in writing the report. This happens because the teachers do not give students the chance to work alone. This study is aimed to describe the increasing ability in writing skills by applying individual task of VIIIF Grade Student of Sekolah Menengah Pertama Negeri 3 Tabanan in academic Year 2012/2013. This research was conducted at Sekolah Menengah Pertama Negeri 3 Tabanan with study subjects was 50 people of VIII F grade students. At the beginning of the study it was showed that 50 % of students received less than 70 which are used as the standard minimum of completeness per individual. The result in pre cycle was 65.80 then in the first cycle increased with an average value of 72.20, and in the second cycle increased to 85. Thus, through the method of writing individual task, ability of the student in writing field trip report was increased.